The Effect of Product Packaging on Firm Performance: A Study on the Food and Beverage Manufacturing Firms in Kenya - Jepchumba, Naomy Jepchumba; Ngugi, Patrick Karanja; Shale, Noor Ismail; Odhiambo, Romanus Odhiambo (International Journal of Supply Chain and Logistics, 2022)
Purpose: In the current 21st century, there has been an increase in changes in the business environment that have forced large-scale enterprises to realign their global strategies and manufacturing activities, and flatten their hierarchies in order to speed up information flows. Food and beverage manufacturing companies in Kenya have been experiencing problems in the performance of their production and operations management. This study therefore, sought to assess the influence of product packaging on the performance of food and beverage manufacturing firms in Kenya. Methodology: A descriptive research design was adopted. Food and beverage manufacturing companies were sampled and the data was collected using self-administered questionnaires and analyzed using descriptive and inferential statistics. Findings: The findings revealed that product packaging had a significant influence on the performance of food and beverage processing firms. The study concluded that product packaging was critical in enhancing the performance of food and beverage processing firms in Kenya. Unique contribution to theory, practice and policy: The study recommends that the management of food and beverage processing firms ought to embrace a product packaging framework in order to gain performance.